Impact of simultaneous hydrolysis of OCP and PLGA on bone induction of a PLGA-OCP composite scaffold in a rat femoral defect. (1st April 2021) - Oizumi, Itsuki; Hamai, Ryo; Shiwaku, Yukari; Mori, Yu; Anada, Takahisa; Baba, Kazuyoshi; Miyatake, Naohisa; Hamada, Soshi; Tsuchiya, Kaori; Nishimura, Shin-nosuke; Itoi, Eiji; Suzuki, Osamu
Abstract: Effect of the simultaneous hydrolysis of octacalcium phosphate (OCP) and poly (lactic-co-glycolic acid) (PLGA) was investigated on its osteoconductivity. PLGA soaked in phosphate buffered saline with 0%, 20%, and 40% OCP at 37°C for eight weeks indicated that when the OCP dose was increased, 1) the weight loss of PLGA increased, 2) the glass transition temperature of the PLGAs decreased, 3) the saturation degree in the saline moved to nearly saturated condition with respect to hydroxyapatite (HA) but was undersaturated with respect to OCP, and 4) OCP tended to convert to HA by X-ray diffraction and Fourier transform infrared spectroscopy. OCP/PLGA composites of 20% and 40% with more than 92% porosity were produced by combining OCP granules with 1, 4-dioxane-solubilizing PLGA followed by lyophilization and then subjected to four- and eight-week in vivo implantation tests in 3 mm diameter rat femora defects. Microfocus X-ray computed tomography, histochemical and histomorphometric analyses showed that while bone formation was very limited with PLGA implantation, the extent of repair tended to increase with increasing OCP content in the PLGA, coupled with PLGA degradation, and bridge the defects with trabecular bone. Tartrate-resistant acid phosphatase-positive osteoclast-like cells were accumulated four weeks after implantation, while osteocalcin-positive osteoblastic cells appeared later at eight weeks, especially in 40% OCP/PLGA. These results suggest that OCP hydrolysis, with phosphate ion release, enhances PLGA hydrolysis, probably through the acid catalysis function of the protons supplied during the hydrolysis of OCP, thereby inducing PLGA biodegradation and new bone formation in the femoral defects. Statement of Significance: Octacalcium phosphate (OCP) enhances osteoblasts and osteocytes differentiations during its hydrolysis accompanying inorganic ions exchange in this material. The present study found that the advancement of OCP hydrolysis under physiological conditions had an effect on poly (lactic-co-glycolic acid) (PLGA) degradation through its chemical environmental change around OCP, which was ascertained by the decreases in weight loss and glass transition temperature of PLGA with increasing the dose of OCP co-present. Rat femur-penetrated standardized severe defects were found to repair through bridging the cortical region defect margin. PLGA degradation could be enhanced through an acid catalyst function by protons derived from inorganic phosphate (Pi) ions through OCP hydrolysis under bone forming condition, resulting in showing a prominent bone regenerative capacity in OCP/PLGA composite materials. Graphical abstract: Image, graphical abstract